Novel de novo pathogenic variant in the ODC1 gene in a girl with developmental delay, alopecia, and dysmorphic features. Issue 12 (21st September 2018) - Bupp, Caleb P.; Schultz, Chad R.; Uhl, Katie L.; Rajasekaran, Surender; Bachmann, André S.
Abstract : The ornithine decarboxylase 1 ( ODC1 ) gene plays an important role in physiological and cell developmental processes including embryogenesis, organogenesis, and neoplastic cell growth. Here, we report an 32‐month‐old Caucasian female with a heterozygous de novo nonsense mutation in the ODC1 gene that leads to a premature abrogation of 14‐aa residues at the ODC protein c‐terminus. This is the first human case confirming similar symptoms observed in a transgenic ODC1 mouse model first described over 20 years ago. Phenotypic manifestations include macrosomia, macrocephaly, developmental delay, alopecia, spasticity, hypotonia, cutaneous vascular malformation, delayed visual maturation, and sensorineural hearing loss. We here describe for the first time a new pediatric disorder that is directly linked to a de novo pathogenic variant in the ODC1 gene. The ODC1 gene mutation (c.1342 A>T) was identified by whole‐exome sequencing and confirmed by Sanger sequencing. Red blood cells obtained from our patient showed elevated ODC protein and polyamine levels compared to healthy controls. Our autosomal dominant patient who carries this gain‐of‐function ODC1 mutation may benefit from treatment with α‐difluoromethylornithine, a well‐tolerated, U.S. Food and Drug Administration (FDA). FDA‐approved drug.